IDENTIFIKASI PENYEBAB DEADFREIGHT MUATAN BATUBARA DI MV. RB MYA - Suharyono; Purwantono; Ningrum Astriawati (Majalah Ilmiah Gema Maritim, 2022)
Muara Berau Anchorage is one of the waters in East Kalimantan that many ships visit for coal loading and unloading activities. The coal export transhipment was carried out in the Berau Estuary, Samarinda because the draft of large ships did not allow it to enter the far and shallow river channel. In the execution of loading there is often a shortage of load caused by several factors. The purpose of the study is to determine the causes and impacts of load deadfreight and efforts to reduce the occurrence of load deadfreight in the coal loading process. The methods used are descriptive qualitative. Data were collected through observation, interviews and literature studies that were tested for validity and reliability tests. The results of this study show that the cause of the load deadfreight in the MV. RB MYA is the theft of cargo along the Mahakam river, spillage of coal cargo during the loading process, and lack of supervision in the loading process at the Jetty. The impact of the deadfreight of coal cargo is the occurrence of a shortage of shiploads and the occurrence of losses for shippers. Efforts were made to reduce the occurrence of payload deadfreights in the MV. RB MYA is to hold barge escorts, increase the effectiveness of communication between the ship and floating cranes, and increase the number of Foreman Jetty.